The Effect of Cash Flow on External Financing, Debt Issuance, and Equity Issuance: The Moderation Role of Board Gender Diversity - Muhammad Faisal Sihite; Dony Abdul Chalid (AIBPM Publisher, 2022)
This paper investigates the relationship between cash flow and external financing and the moderating effect of board gender diversity. It aims to explain how cash flow affects external financing with three proxies of Equity Issuance, Debt Issuance, and External Financing. This study explains how Board Gender Diversity influences Cash Flow and External Financing. This study took a sample of a company listed in the Indonesia Stock Exchange from 2014 until 2019 and used Ordinary Least Square (OLS) for the regression method. The findings indicate a negative correlation between Cash Flow and External Financing. Addedly, Board Gender Diversity insignificantly affects the moderation between Cash Flow and External Financing. Keywords: Board Gender Diversity, Cash Flow, Debt Issuance, Equity Issuance, External Financing